Svetozar Marković – the predecessor of historical sociology and the founder of socialist thought and movement in Serbia and the Balkans - Mitrović, Ljubiša R. (Sociološki pregled, 2026)
The paper analyzes the personality and work of Svetozar Marković as the teacher of emancipatory energy, the predecessor of historical sociology in our country and the founder of socialist thought and the socialist movement in Serbia and the Balkans. First, there is an overview of the role of great “sunny personalities”, eternal star lanterns, those who awaken the people, in national history and collective memory. This is followed by a brief biographical review of Svetozar Markopvić’s personality and work (1846–1875). The central subject of our sociological examination is Marković’s contribution to historical sociology and the importance of re-actualizing his socialist thoughts and messages about the workers’ question of “bread and self-government” in the context of post-socialist societies in the Balkans, to the revival of today’s left wing.